Activities of aztreonam in combination with several novel β-lactam-β-lactamase inhibitor combinations against carbapenem-resistant Klebsiella pneumoniae strains coproducing KPC and NDM - Li, Xinhui; Zhang, Jisheng; Wang, Jianmin; Long, Wenzhang; Liang, Xushan; Yang, Yang; Gong, Xue; Li, Jie; Liu, Longjin; Zhang, Xiaoli (Frontiers in Microbiology, 2024)
Coproducing-serine/metallo-carbapenems isolates, are a serious emerging public health threat given their rapid dissemination and the limited number of treatment options. The purposes of this study were to evaluate the in vitro antibacterial activity of novel β-Lactam-β-Lactamase Inhibitor Combinations (BLBLIs) against Carbapenem-resistant Klebsiella pneumoniae (CRKP) coproducing metallo-β-lactamase and serine-β-lactamase, and to explore the effects in combination with aztreonam, meropenem, or polymyxin, to seek the best therapeutic options. Four CRKP isolates coproducing K. pneumoniae carbapenemase (KPC) and New Delhi metallo-β-lactamase (NDM) were selected and of aztreonam combined with CZA was inferior to that of MEV. Compared with the same concentration of aztreonam plus CZA combination, aztreonam/avibactam had better bactericidal effect (24h bacterial count reduction > 3 log 10 CFU/mL). The above datas indicated that the combination of ATM with several new BLBLIs had powerful bactericidal activity, which suggest these double β-lactam combinations might provide potential alternative treatments for infections caused by coproducing-serine/metallo-carbapenems pathogens.